(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2024)
The present study aimed to investigate and determine the most relevant fertilization levels of Simple Superphosphate to increase fruit production and improve fruit quality for fresh consumption. The experiment was conducted at the EPAMIG Experimental Field in Lambarí, Minas Gerais, from September 2021 to November 2022. Five fertilization levels were tested: 150 grams/plot, 300 grams/plot, 600 grams/plot, and 1200 grams/plot, along with a control group (no fertilization). A significant increase in fruit production was observed at the higher dose (1200 grams/plot) compared to the control, representing a 54.06% increase in fruit production. Additionally, the total fresh biomass production increased by 19.43%, the number of primary and secondary branches per plant increased by 48.99%, the branch length increased by 4.26%, and the canopy diameter increased by 6.83% when compared to the control. All these characteristics were significantly different at the 95% confidence level according to the Scott-Knott test. We concluded that 300 grams/plot was the best fertilization dose to achieve higher production and acceptable quality.